CAPACITY BUILDING OF THE SUKABUMI CITY LABOR OFFICE IN THE ABSORPTION OF LABOR IN THE CITY OF SUKABUMI - Giandini Rizkia; Andi Mulyadi; M. Rijal Amirullah (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2025)
The Sukabumi City Manpower Service is an element implementing the technical tasks of regional autonomy which has the task of regional government affairs based on the principle of regional autonomy, as well as carrying out the functions of formulating policies, administering government affairs and coaching and implementation in accordance with the scope of its duties. The purpose of this research is to find out how the Capacity Building of the Sukabumi City Manpower Office is absorbing labor. The background to this research is the lack of quality and quantity of instructors, the absence of functional training instructors owned by the Sukabumi City Manpower Office, and the still limited modules and standards for job training, which affects the process, capacity and quality of training. This research uses theory according to Grindle (1997:5) with three dimensions. The method used in this research is qualitative with a descriptive approach, as well as data collection through observation, interviews and documentation. The results of this research show that various programs carried out by the Manpower Department have been running but have not been effective, seen from the lack of job training instructors and the lack of supporting facilities and infrastructure.